LITERATURE STUDY OF THE ENVIRONMENTAL IMPACT ASSESSMENT AND LIFE CYCLE OF GEOPLYMER MORTAR MATERIAL AS A LOW-CARBON ALTERNATIVE - Dimas Lambang Ramadhani; Zhang Yichao (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
The manufacturing of intensive cement requires a lot of energy, which leads to large greenhouse gas (GHG) emissions, and the conventional concrete (CC) is notorious for having a big environmental impact. This study offers a thorough analysis of the literature on the life cycle and environmental impact evaluation of geopolymer mortar materials, investigating them as a low-carbon substitute for conventional concrete. Concrete types covered by the analysis include self-healing geopolymer concrete (SHGPC), conventional concrete (CC), and geopolymer concrete (GC). The findings indicate that GC offers substantial environmental benefits over CC, particularly in terms of climate change mitigation and fossil depletion, due to the use of fly ash and silica fume. However, the chemical activators in GC, such as NaOH and Na2SiO3, have significant negative impacts on human health and freshwater ecosystems. Additionally, while SHGPC reduces global warming potential, it increases fossil fuel consumption and ozone depletion due to sodium silicate production and self-healing microcapsule synthesis. Transportation of raw materials like fly ash and silica fume also plays a crucial role in the overall environmental impact but can be minimized by sourcing locally. This review highlights the need for further research and development in optimizing geopolymer production processes, utilizing local materials, and enhancing self-healing technologies to promote sustainable construction practices.